2020
DOI: 10.14214/df.292
|View full text |Cite
|
Sign up to set email alerts
|

Wood utilization scenarios and their sustainability impacts in Finland

Abstract: Social, economic and environmental impacts vary in different wood utilization patterns, and national level strategies should consider possible trade-offs and regional needs. This thesis explored a variety of wood utilization scenarios in Finland and assessed their possible future benefits and trade-offs in environmental, economic and social sustainability, forming plausible pathways to actualize preferred outcomes reflecting different priorities in the goal setting. The research was conducted by using model-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
(126 reference statements)
1
0
0
Order By: Relevance
“…A recent study also confirmed our results that shifting secondary wood flows e.g. industrial side streams and endof-life wood-based products from energy uses to material uses, results in increased climate benefits (Kunttu, 2020). We also found that the level of carbon stored in HWP can be increased by changing the wood assortment structure while maintaining the same level of volume felled, which is consistent with existing literature (Parobek et al, 2019;Pilli et al, 2015).…”
Section: A Co 2 Cumulative Gross Emission Bioenergy and Wood Oxidatio...supporting
confidence: 92%
“…A recent study also confirmed our results that shifting secondary wood flows e.g. industrial side streams and endof-life wood-based products from energy uses to material uses, results in increased climate benefits (Kunttu, 2020). We also found that the level of carbon stored in HWP can be increased by changing the wood assortment structure while maintaining the same level of volume felled, which is consistent with existing literature (Parobek et al, 2019;Pilli et al, 2015).…”
Section: A Co 2 Cumulative Gross Emission Bioenergy and Wood Oxidatio...supporting
confidence: 92%